Human platelet lysates for human cell propagation. (17th February 2021) - Barro, Lassina; Burnouf, Pierre-Alain; Chou, Ming-Li; Nebie, Ouada; Wu, Yu-Wen; Chen, Ming-Sheng; Radosevic, Miryana; Knutson, Folke; Burnouf, Thierry
Abstract: A pathogen-free and standardized xeno-free supplement of growth media is required for the ex vivo propagation of human cells used as advanced therapeutic medicinal products and for clinical translation in regenerative medicine and cell therapies. Human platelet lysate (HPL) made from therapeutic-grade platelet concentrate (PC) is increasingly regarded as being an efficient xeno-free alternative growth medium supplement to fetal bovine serum (FBS) for clinical-grade isolation and/or propagation of human cells. Most experimental studies establishing the superiority of HPL over FBS were conducted using mesenchymal stromal cells (MSCs) from bone marrow or adipose tissues. Data almost unanimously concur that MSCs expanded in a media supplemented with HPL have improved proliferation, shorter doubling times, and preserved clonogenicity, immunophenotype, in vitro trilineage differentiation capacity, and T-cell immunosuppressive activity. HPL can also be substituted for FBS when propagating MSCs from various other tissue sources, including Wharton jelly, the umbilical cord, amniotic fluid, dental pulp, periodontal ligaments, and apical papillae. Interestingly, HPL xeno-free supplementation is also proving successful for expanding human-differentiated cells, including chondrocytes, corneal endothelium and corneal epithelium cells, and tenocytes, for transplantation and tissue-engineering applications. In addition, the most recent developments suggest the possibility of successfully expanding immune cells such as macrophages, dendritic cells, and chimeric antigen receptor-T cells in HPL, further broadening its use as a growth medium supplement. Therefore, strong scientific rationale supports the use of HPL as a universal growth medium supplement for isolating and propagating therapeutic human cells for transplantation and tissue engineering. Efforts are underway to ensure optimal standardization and pathogen safety of HPL to secure its reliability for clinical-grade cell-therapy and regenerative medicine products and tissue engineering.